Beginning Reading Development of Deaf Learners in Primary Education - Gil Jr., Tyrone O. (Educative: Jurnal Ilmiah Pendidikan, 2025)
This paper is geared towards exploring how beginning reading development happen among Deaf learners in the primary grades. By reviewing several studies that were conducted related to beginning reading for young Deaf learners, the researcher extracted significant and relevant information on language and reading development for deaf learners. Effective reading strategies were also methodically identified as a recommendation for teachers to use in teaching DHH. The first part of the paper will explore on the language development of Deaf learners which is essential in understanding reading development. Furthermore, the reading development will be discussed vis-à-vis the Simple View of Reading theory by Gough and Tumner (1986). Several, reading strategies will also be discussed such as total communication, shared reading activities, and direct and mediated instruction. Finally, the paper concludes for careful planning of reading interventions that is theoretically-based and data driven.